Wiring pada miniatur Smart Home Bertenaga Surya - Muhammad Sakhalish Zayyan; Juan Edo Mikrado; Irrine B Sulistiawati; Aryuanto Soetedjo; Komang Somawirata; Sotyohadi (FORTEI Regional VII Jawa Timur, 2022)
Smart Home technology has existed and developed for more than a decade. According to the Smart Home Association (smart home) the best definition of Smart Home is the integration of technology and services through a home network for a better quality of life. The main purpose of this article is to introduce children to smart home by making a miniature smart home using HMI Haiwell SCADA, Outseal PLC Arduino Mega and other components. This article uses SCADA, the RS 485 control protocol to create this miniature smart home. Previously, if the user wanted to control the equipment, he had to move near the wall and control the switch. This method is less comfortable for parents and people with special needs. A smart home that can be controlled and controlled remotely is an alternative solution. This miniature smart home uses solar panels as an energy source so when there is a blackout, this miniature can still be used.